2013
DOI: 10.3892/ijmm.2013.1358
|View full text |Cite
|
Sign up to set email alerts
|

Nitidine chloride inhibits hepatocellular carcinoma cell growth in vivo through the suppression of the JAK1/STAT3 signaling pathway

Abstract: Abstract. Signal transducer and activator of transcription 3 (STAT3) is persistently activated in cancer cells and contributes to malignant progression in various types of cancer. The Janus-activated kinase (JAK) family phosphorylates STAT3 in response to stimulation by cytokines or growth factors. The JAK1-STAT3 signaling pathway plays an important role in cell proliferation and apoptosis. Nitidine chloride (NC) is a benzophenanthridine alkaloid that has been reported as an antitumor agent due to its its inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 39 publications
(42 reference statements)
2
54
0
Order By: Relevance
“…Alkaloids, mainly found in the root or the stem bark of Z. simulans have been of immense interest due to their bioactivities, and quaternary alkaloids (QAs) as major alkaloids in this plant possess significant antitumour activities. For instance, nitidine displayed inhibitory activity on hepatic carcinoma cells by inhibiting the JAK1/STAT3 signal pathway in vitro , chelerythridine and sanguinarine showed dose‐dependent inhibitory activity by damaging the DNA of leukaemia carcinoma cells (L1210) in vitro , and fagaronine acted as angiogenesis inhibitors on leukaemia cancer cells . To explore the antitumour activities and the subsequent mechanisms of action regarding QAs from Z. simulans , one of the most important steps is to enrich and identify them from complex crude plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids, mainly found in the root or the stem bark of Z. simulans have been of immense interest due to their bioactivities, and quaternary alkaloids (QAs) as major alkaloids in this plant possess significant antitumour activities. For instance, nitidine displayed inhibitory activity on hepatic carcinoma cells by inhibiting the JAK1/STAT3 signal pathway in vitro , chelerythridine and sanguinarine showed dose‐dependent inhibitory activity by damaging the DNA of leukaemia carcinoma cells (L1210) in vitro , and fagaronine acted as angiogenesis inhibitors on leukaemia cancer cells . To explore the antitumour activities and the subsequent mechanisms of action regarding QAs from Z. simulans , one of the most important steps is to enrich and identify them from complex crude plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the tumor-selective cytotoxicity of NC was found to be attributed to intercalation into DNA and inhibition of topoisomerase I and II (Gatto et al, 1996;Holden et al, 1999;Iwasaki et al, 2010;Pan et al, 2011). Additionally, NC could inhibit hepatocellular carcinoma cell growth in vivo (Liu et al, 2009;Liao et al, 2013). Thus, NC is thought to be a promising anticancer drug candidate.…”
Section: Introductionmentioning
confidence: 99%
“…DC (Arthur et al, 1959), was reported to have significant antimalarial (Gakunju et al, 1995), anti-human immunodeficiency virus (Tan et al, 1991), antimicrobial, and analgesic activities (Del Poeta et al, 1999;Hu et al, 2006). Recently, a number of studies found that NC showed anticancer potential in several tumor types, including osteosarcoma, gastric cancer, and liver cancer (Lv et al, 2011;Chen et al, 2012;Liao et al, 2013). The anticancer activity of NC was correlated with its ability to decrease cell growth, induce cell apoptosis, and arrest cell cycles in a variety of human cancer cell lines, such as MG-63 and KB osteosarcoma cell lines (Liu et al, 2007;Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is the second cause of cancer-related mortality in China, and its prevalence is increasing, probably due to a high prevalence of hepatitis B (2,3). Surgical resection and liver transplantation are effective forms of therapy (4), but most patients have limited options and cannot afford these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy cells, activation of the STAT3 protein is tightly controlled, in order to prevent deregulated gene transcription. STAT3 is constitutively activated in certain transformed cells (3). STAT3 activation is induced via phosphorylation of tyrosine (Tyr705), which allows STAT3 dimerization.…”
Section: Introductionmentioning
confidence: 99%